Writing and publishing music theory in early seventeenth-century Italy: Adriano Banchieri and his contemporaries - Ballantyne, AL (2014)
Why write music theory and publish it? In the thesis I investigate the reasons for a seeming over-abundance of practically oriented music treatises in early seventeenth-century Italy. Throughout I challenge our conventional assessment of the study of music theory: I suggest that we can define a music-theoretical text in terms of its material form in addition to its content. Adriano Banchieri (1568-1634) was the most prolific theorist in early seventeenth-century Italy. His music-theory books exemplify contemporary printing patterns, an overt practical focus, and a synthesis of contemporary theoretical innovations. In Chapter 1, after considering the meaning of 'music theory' and how it is typically classified, I discuss the process of and purposes for writing and publishing music theory. In Chapter 2 I explore Banchieri's practical and philosophical motives for writing music theory, and thus introduce the reader to his music-theoretical corpus. The focus of the thesis then broadens: in Chapter 3 I survey the typical authors, publishing houses, content, material form, function and readers of the various kinds of theoretical texts printed in Italy between 1600 and 1630. In Chapter 4 I examine the widespread practice of publishing second and revised editions of music-theory books in order to establish the extent to which a new edition corresponds to a seeming demand for a particular text. The case study of the paratext of Banchieri's Conclusiones de musica (Bologna, 1627) in Chapter 5 demonstrates the great extent to which the preliminary matter of an early Seicento music-theory book is embedded in its socio-cultural context and how a paratext projects ideas contained in the text proper. Lastly, in Chapter 6 I explore to whom and in which particular forums theoretical writings circulated. Here I focus principally on Banchieri's printed letters, which provide evidence of how an author circulated his music books.